Extended Intake of Mulberry Leaf Extract Delayed Metformin Elimination via Inhibiting the Organic Cation Transporter 2 - Hyun Wook Huh; Young-Guk Na; Ki-Hyun Bang; Sung-Jin Kim; Minki Kim; Kyung-Tae Kim; Jong-Seong Kang; Young-Ho Kim; Jong-Suep Baek; Hong-Ki Lee; Cheong-Weon Cho (MDPI AG, 2020)
Diabetes mellitus (DM) has become a major health problem in most countries of the world. DM causes many complications, including hyperglycemia, diabetic ketoacidosis, and death. In Asia, mulberry has been used widely in the treatment of DM. Combination of drugs with herbal medicine may reduce the unwanted side effects caused by drugs. In this study, the influence of extended mulberry leaves extract (MLE) intake on metformin (Met) was evaluated in terms of pharmacokinetics and pharmacodynamics in DM-induced rats. Three week-treatment of MLE alone produced the anti-hyperglycemic effect (around 24%) if compared to the control. Interestingly, Met administration after MLE treatment for 3 weeks enhanced about 49% of the anti-hyperglycemic effect of Met. In addition, the extended intake of MLE potentiated the anti-hyperglycemic effect of Met on various concentrations. This potentiated anti-hyperglycemic effect of Met appears to be due to the pharmacokinetic change of Met. In this study, 3 week-treatment of MLE reduced the elimination of Met in DM-induced rats. In addition, MLE reduced the human organic cation transporter 2 (hOCT2) activity in a concentration-dependent manner. Thus, these findings suggest that MLE lowered the elimination of Met via inhibiting the hOCT2.